Hubungan antara Metode Audiolingual dengan Penguasaan Keterampilan Bahasa Jepang Peserta di LKP Harapan Mandiri Ambulu Jember - Adi Kurniawan (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
The purpose of this study was to determine the relationship between the audiolingual method and the Japanese language proficiency of participants at LKP Harapan Mandiri Ambulu Jember. This study used a correlational quantitative method. The research location was determined using the purposive area technique. The respondent selection technique in this study used total sampling with a population of 35 people at LKP Harapan Mandiri Ambulu Jember. The results of the Spearman rank correlation showed that the audiolingual method had a very high relationship with the Japanese language proficiency of participants at LKP Harapan Mandiri Ambulu Jember with a correlation coefficient of 0.842 (interpretation of a very high correlation value) at a significance level of 5%, which was greater than the r-table value of 0.333. In this case, the null hypothesis in this study is rejected and the alternative hypothesis is accepted. In addition, the results of the analysis of the first indicator of the audiolingual method show that listening exercises have a high correlation with the Japanese language proficiency of participants at LKP Harapan Mandiri Ambulu Jember, while the indicator of word and sentence pronunciation exercises has a very high correlation with the Japanese language proficiency of participants at LKP Harapan Mandiri Ambulu Jember. Therefore, it can be concluded that the audiolingual method plays a significant role in improving Japanese language skills. Thus, the results of this study support the hypothesis that there is a relationship between the audiolingual method and the Japanese language skills of participants at LKP Harapan Mandiri Ambulu Jember.
Approved by Teddy
Keywords: Training Method; Audiolingual Method; Japanese Language Skills